Improved spectral descriptions of planetary nebulae central stars - Weidmann, Walter Alfredo (2015)
Context. At least 492 central stars of Galactic planetary nebulae (CSPNs) have been assigned spectral types. Since many CSPNs are faint, these classification efforts are frequently made at low spectral resolution. However, the stellar Balmer absorption lines are contaminated with nebular emission; therefore in many cases a low-resolution spectrum does not enable the determination of the H abundance in the CSPN photosphere. Whether or not the photosphere is H deficient is arguably the most important fact we should expect to extract from the CSPN spectrum, and should be the basis for an adequate spectral classification system. Aims. Our purpose is to provide accurate spectral classifications and contribute to the knowledge of central stars of planetary nebulae and stellar evolution. Methods. We have obtained and studied higher quality spectra of CSPNs described in the literature as weak emission-line star (WELS). We provide descriptions of 19 CSPN spectra. These stars had been previously classified at low spectral resolution. We used medium-resolution spectra taken with the Gemini Multi-Object Spectrograph (GMOS). We provide spectral types in the Morgan-Keenan (MK) system whenever possible. Results. Twelve stars in our sample appear to have normal H rich photospheric abundances, and five stars remain unclassified. The rest (two) are most probably H deficient. Of all central stars described by other authors as WELS, we find that at least 26% of them are, in fact, H rich O stars, and at least 3% are H deficient. This supports the suggestion that the denomination WELS should not be taken as a spectral type, because, as a WELS is based on low-resolution spectra, it cannot provide enough information about the photospheric H abundance.